Changes in air pollution levels after COVID-19 outbreak in Korea (2020)
In order to control the spread of COVID-19, social distancing measures were implemented in many countries. This study investigated changes in air pollution during the social distancing after the COVID-19 outbreak in Korea. Ambient PM2.5, PM10, NO2, and CO that are particularly related to industrial activities and traffic were reduced during the social distancing in response to the COVID-19 outbreak. In March 2020, immediately after social distancing, mean levels of PM2.5, PM10, NO2, and CO decreased nationwide from last year's mean levels by 16.98 μg/ m3 , 21.61 μg/m3 , 4.16 ppb, and 0.09 ppm, respectively (p-value for the year-to-year difference <0.001, =0.001, = 0.008, <0.001), a decrease by 45.45%, 35.56%, 20.41%, and 17.33%, respectively. Changes in ambient O3 or SO2 were not observed to be attributable to social distancing. Our findings, that such effort for a short period of time resulted in a significant reduction in air pollution, may point toward reducing air pollution as a public health problem in a more sustainable post-COVID-19 world.